The SAHR Setup-Controlling Hopping Speed and Height Using a Single Actuator - N. Cherouvim; E. Papadopoulos (Applied Bionics and Biomechanics)
In this paper we present and experimentally validate a control method for regulating both the forward speed and the apex height of a one-legged hopping robot, using only a single actuator. The control method is based on a dynamic model of the hopping robot and makes use of the dynamic coupling of the vertical and forward motions of the robot. The control is applied first to a simulated model of the robot and shown to track a desired forward robot speed and a desired apex height. Then the SAHR (single actuator hopping robot) hardware is introduced and is used as an experimental platform with which to evaluate the performance of the control method. The control method is applied to the physical setup and is shown to lead to a stable hopping gait with a desired forward speed and apex height, despite the unmodelled disturbances met on the laboratory floor.